Mind : a journey to the heart of being human - Siegel, Daniel J., 1957- (W.W. Norton & Company, 2017)
"What is the mind? What is the experience of the self truly made of? How does the mind differ from the brain? Though the minds contentsits emotions, thoughts, and memories--are often described, the essence of mind is rarely, if ever, defined. In this book, noted neuropsychiatrist and New York Times best-selling author Daniel J. Siegel, MD, uses his characteristic sensitivity and interdisciplinary background to offer a definition of the mind that illuminates the how, what, when, where, and even why of who we are, of what the mind is, and what the minds self has the potential to become. MIND takes the reader on a deep personal and scientific journey into consciousness, subjective experience, and information processing, uncovering the minds self-organizational properties that emerge from both the body and the relationships we have with one another, and with the world around us. While making a wide range of sciences accessible and excitingfrom neurobiology to quantum physics, anthropology to psychologythis book offers an experience that addresses some of our most pressing personal and global questions about identity, connection, and the cultivation of well-being in our lives,"--Amazon.com.